The jungle book - Kipling, Rudyard 1865-1936.; Robson, W. W. (William Wallace) 1923- . (Oxford New York Oxford University Press, 1987)
Presents the adventures of Mowgli, a boy reared by a pack of wolves, and the wild animals of the jungle. Also includes other short stories set in India.
Bibliography: p. [xxxi]-xxxiii.
Keywords: Mowgli (Fictitious character) -- Fiction; Adventure stories, English; Jungle animals -- Fiction; Feral children -- Fiction; Jungles -- Fiction; Animals -- Fiction; Short stories; India -- Fiction; India -- Fiction